Intra-site variability in lithic recycling at Qesem Cave, Israel. (10th March 2015) - Assaf, Ella; Parush, Yoni; Gopher, Avi; Barkai, Ran
Abstract: This paper presents new results regarding lithic recycling in three flint assemblages from Qesem Cave, a late Lower Paleolithic site in Israel assigned to the Acheulo-Yabrudian Cultural Complex (AYCC). The study focuses on the similarities and differences in lithic recycling at the cave between the Amudian and Yabrudian industries as well as within the Amudian industry. Variability in recycling is evident at both the inter-industry level (between the Amudian and Yabrudian) and the intra-industry level (within the Amudian). In light of the results, we discuss the role of lithic recycling in the two AYCC industries at Qesem Cave, shedding new light on AYCC lithic variability in general and human behavior at Qesem Cave in particular.